2010
DOI: 10.2214/ajr.10.4923
|View full text |Cite
|
Sign up to set email alerts
|

A Systematic Review of the Factors Affecting Accuracy of SUV Measurements

Abstract: Scanner and reconstruction parameters can significantly affect SUV measurements. When using serial SUV measurements to assess early response to therapy, imaging should be performed on the same scanner using the same image acquisition and reconstruction protocols. In addition, attention to detail is required for accurate determination of the administered radiopharmaceutical dose.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

10
381
2
14

Year Published

2013
2013
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 522 publications
(407 citation statements)
references
References 40 publications
10
381
2
14
Order By: Relevance
“…Furthermore, a number of biological and technological factors influence the measurement of SUV max (21). Therefore, the exploration of other metabolic parameters is required.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, a number of biological and technological factors influence the measurement of SUV max (21). Therefore, the exploration of other metabolic parameters is required.…”
Section: Discussionmentioning
confidence: 99%
“…However, we noted that in Case 2, biopsied to be benign lupus lymphadenitis, the SUVmax was 13.2. Importantly, PET scanner and reconstruction methods are factors that intimately affect SUV measurements and stringent quality control measures are necessary when comparing studies [11].…”
Section: Discussionmentioning
confidence: 99%
“…The SUV max cutoff value in our study was thus lower than previously reported. The reason for this descrepancy may be that a large number of factors affect SUV measurements; these factors principally consist of biological factors such as body size, blood glucose levels, and patient breathing, as well as technological factors including interscanner variability, image reconstruction parameters, injected radioactivity, and the use of CT contrast material (13). Our study has some limitations: 1) we enrolled a small number of patients from a single center and performed retrospective analysis, which could lead to selection bias.…”
Section: Discussionmentioning
confidence: 99%